Pengembangan MODISA (Modul Pendidikan Seks Bagi Remaja) Untuk Mencegah Perilaku Seks Bebas Pada Siswa SMA - Cindy Aprillia; Dian Purbo Utomo (BRILIANT: Jurnal Riset dan Konseptual, 2026)
The research was motivated by the increasing sexual behavior among adolescents due to low knowledge, environmental influences, and a lack of sex education. Therefore, MODISA was developed as a means of preventing promiscuous sexual behavior. The research aims to describe adolescents' understanding of sex education, map existing prevention efforts, and develop relevant, interesting, and appropriate modules. The method used in Research and Development with the ADDIE model includes the stages of analysis, design, development, implementation, and evaluation, which is limited to the development stage in the form of testing the feasibility of the module by experts and prospective users. Interview data analysis used the Miles and Huberman interactive model assisted by MAXQDA 2026 software, while the product acceptability analysis used the inter-rater agreement model. The results of the MODISA research respond to the needs of students and guidance counselors for comprehensive, easy-to-understand sex education materials equipped with illustrations. The validity test results obtained were 1.00 from material experts, media experts, and prospective users, thus indicating the validity results are in the very high category, meaning MODISA is very appropriate, very useful, very interesting, and very feasible to use. In conclusion, MODISA (Sex Education Module for Teenagers) has the potential to improve adolescents' knowledge, attitudes, and behavior towards the risks of sexual behavior, so that it can be a structured teaching material for high school guidance and counseling teachers in providing sex education.